Identifikasi Bangunan-Bangunan Peninggalan Sejarah Masa Kolonial Belanda di Pesisir Timur Aceh - Anis, Madhan; Ramazan, Ramazan; Prasetyo, Okhaifi; Nuryanti, Reni; Safitri, Intan; Mauladi, Wiwin; Puspita, Maya; Rahayu, Mutiara (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
The Dutch colonial presence in the eastern coastal region of Aceh had a significant influence on infrastructure development and cultural changes in the area. The buildings left over from the Dutch Colonial period on the East Coast of Aceh are physical evidence of the interaction between the Dutch and the people of Aceh at that time. Therefore, these relics must be protected and preserved. A lack of public understanding of the importance of preserving cultural heritage can result in neglect and lack of support for the preservation of these buildings. For this reason, the aim of this research is to identify buildings left over from the Dutch Colonial period in the cities on the East coast of Aceh, such as East Aceh, Langsa City, and Aceh Tamiang. The research used in this research is historical or historical research methods. The steps in historical research are heuristics, verification, interpretation, and historiography. As a result of the research that has been carried out, a number of locations of historical heritage building objects were found scattered at several points in East Aceh, Langsa City, and Aceh Tamiang. In East Aceh, the East Aceh Regent's Hall and the Water Storage Reservoir are historical heritage sites. Langsa City also has several historical heritage buildings, such as the Balee Juang Building, SD Negeri 1 Langsa, PDAM, Hall, Satpol PP and WH Building, and Langsa Post Office. Apart from that, in Aceh Tamiang, there is a Regent's pavilion building and a Dutch rubber plantation industrial building, which are important historical relics. These historical remains provide an overview of the cultural and historical heritage of the area.Kehadiran Kolonial Belanda di wilayah pesisir Timur Aceh membawa pengaruh yang signifikan dalam pembangunan infrastruktur dan perubahan budaya di daerah tersebut. Bangunan-bangunan peninggalan masa Kolonial Belanda di Pesisir Timur Aceh menjadi bukti fisik dari interaksi antara Belanda dan masyarakat Aceh pada masa itu. Oleh karena itu, peninggalan tersebut harus dilindungi dan dilestarikan. Kurangnya pemahaman masyarakat tentang pentingnya melestarikan warisan budaya dapat mengakibatkan penelantaran dan kurangnya dukungan untuk pelestarian bangunan-bangunan tersebut. Untuk itu tujuan penelitian ini yakni mengindetifikasi bangunan-bangunan peninggalan masa Kolonial Belanda di Kota pesisir Timur Aceh seperti di Aceh Timur, Kota Langsa dan Aceh Tamiang. Penelitian yang digunakan dalam penelitian ini adalah metode penelitian sejarah atau historis. Langkah-langkah penelitian sejarah yaitu, heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian yang telah dilakukan, ditemukan sejumlah lokasi objek bangunan peninggalan sejarah yang tersebar di beberapa titik di Aceh Timur, Kota Langsa, dan Aceh Tamiang. Di Aceh Timur, terdapat Pendopo Bupati Aceh Timur dan Waduk Penampung Air sebagai peninggalan bersejarah. Kota Langsa juga memiliki beberapa bangunan peninggalan sejarah seperti Gedung Balee Juang, SD Negeri 1 Langsa, PDAM, Pendopo, Gedung Satpol PP dan WH, dan Kantor Pos Langsa. Selain itu, di Aceh Tamiang terdapat gedung pendopo Bupati dan  bangunan industri perkebunan karet Belanda yang menjadi peninggalan sejarah yang penting. Peninggalan sejarah tersebut memberikan gambaran tentang warisan budaya dan sejarah daerah tersebut.